Tourism Fuels an Emerging City: The Case of Tagbilaran City, Bohol - Fatima del Prado; Iris L. Acejo; Darlyne Remolino (Philippine Institute for Development Studies (PIDS), 2004)
This paper traces the urbanization experience of Tagbilaran City, Bohol taking into account the demographic development that took place, as well as the perceived contribution of tourism in the citys quest to firmly establish and improve its urban status. It also looks into the nature and magnitude of government responses to the demands of increasing urbanization, at the same time examines the citys attempts to benefit from the influx of tourists as Bohol Province attains national and international distinction of being one of the countrys top tourist destinations.
Keywords: 330; urbanization; local governance; emerging city; Tagbilaran City